Effect of Aspect and Tillage Practices on Growth and Yield Attributes of Kalmegh (Andrographis Paniculata) - Sanwal, C. S.; Lone, Raheel Anwar; Sushma; Khan, P. A.; Pant, K. S.; Bhardwaj, S. D. (Indian Forester, 2015)
The appropriate aspect of a mountainous slope coupled with suitable tillage practice can make very significant influences on the growth and yield attribute of a cultivated plant species especially in degraded land. So present paper aims to evaluate the effect of aspect and tillage practices on growth and yield attributes of Andrographis paniculata when raised in degraded or wasteland of mountainous area. A. paniculata was grown on three topographical aspects viz Northern, North western and Western at a spacing of 30 cm Ã— 30 cm, followed by three tillage depths viz minimum (0 cm), medium (up to 10 cm) and deep tillage (up to 15 cm). Growth attributes like plant height, number of branches per plant, leaf area index and yield showed significant difference with respect to aspect and tillage practices and highest growth and yield attributes were found when herb was grown on western aspect under deep tillage. Thus the knowledge and selection of suitable geographical aspect and tillage practice for raising A. paniculata can be helpful in cost effectiveand environment friendly cultivation with the optimum yields in degraded mountainous area.